1989
DOI: 10.1159/000177544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre- and Postnatal Protein Undernutrition on Glycemia, Ketonemia and Liver Glycogen Concentration in Suckling Rats

Abstract: Pregnant Wistar rats were fed ad libitum diets containing either 25% (control) or 8 % casein (undernourished) from conception through the gestation and lactation periods. Rats from undernourished dams had lower birth weights than control rats and this difference persisted up to day 21 of postnatal life. Livers obtained from undernourished animals aged 10, 15 and 20 days weighed 50% less than control livers. Liver glycogen concentration was much higher in 7- and 10-day-old undernourished rats than in normal rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…Early undernutrition enhances insulin sensitivity in extrahepatic tissues, such as muscle and adipose tissue, in adulthood (16,18,27,45), but the impact of this restriction on the adult or immature liver has been less frequently addressed. Suckling rats from dams on hypoproteic diets throughout pregnancy and lactation show increased hepatic glycogen (21,26), as found herein in pups from globally restricted rats, indicating that this response is independent of the type of restriction. The increased amounts of GLUTs and GS and the low levels of GP suggest elevated rates of glucose uptake and glycogen production, which is supported by reduced hepatic contents of free glucose and lactate.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Early undernutrition enhances insulin sensitivity in extrahepatic tissues, such as muscle and adipose tissue, in adulthood (16,18,27,45), but the impact of this restriction on the adult or immature liver has been less frequently addressed. Suckling rats from dams on hypoproteic diets throughout pregnancy and lactation show increased hepatic glycogen (21,26), as found herein in pups from globally restricted rats, indicating that this response is independent of the type of restriction. The increased amounts of GLUTs and GS and the low levels of GP suggest elevated rates of glucose uptake and glycogen production, which is supported by reduced hepatic contents of free glucose and lactate.…”
Section: Discussionsupporting
confidence: 73%
“…To maintain its high growth rate, the developing brain is supplied with glucose and ketone bodies (14). We found that the decrease in plasma glucose associated with undernutrition was accompanied by a rise in ketone bodies, as reported in models of specific protein restriction (21), showing that this adaptation is independent of the type of restriction. In adults, brain glucose consumption slows down with prolonged fasting, a condition that enhances cerebral ketone body extraction from blood.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly malnutrition after weaning exerted a similar effect as early malnutrition leading to similar deficit of body weight. Many studies have focused on analyzing the effects of malnutrition during gestation and lactation 15, 30, 31 but have not explored the effects of protein malnutrition in later periods of accelerated growth, like the immediately post-weaning period. During this interval from weaning to 55 days, rats still undergo a fast growth spurt and our results show that during this period the young rats are most vulnerable to the effects of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In the low-protein diet, carbohydrate (corn starch) isocalorically replaced protein. The composition of these two diets has been essentially described before (Gamallo et al 1989). Diets were administered during the 5 weeks prior to conception and through the gestation and lactation periods.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Pre-and postnatal protein undernutrition produces a great number of metabolic and structural alterations in the suckling rat (Morgane, Miller, Kemper, Stern, Forbes, Hall, Bronzine, Kissane, Hawrylewicz and Resnick 1978;Yeh, Zee, Owen and Walker 1982;Perry, Gamallo and Bernard 1986;Gamallo, Perry, Trindade, Pereira and Bernard 1989). We have previously reported that maternal protein undernutrition leads to the appearance of hyperketonemia in the rat pup (Gamallo et al 1989).…”
Section: Introductionmentioning
confidence: 96%